1981
DOI: 10.1007/bf01971780
|View full text |Cite
|
Sign up to set email alerts
|

Avermectins: novel insecticides, acaricides and nematicides from a soil microorganism

Abstract: terone in stimulating reptilian oxidative metabolism. This is interesting since oestrogen has many important biological actions opposite to those of testosterone. There are only a few reports on the effects of oestrogens on oxidative metabolism of lower vertebrates. Hoar 8 injected goldfish with stilbesterol and observed a marked stimulation of oxidative metabolism. He offered the suggestion that the steroid may increase in some way the reactivity of 963 neuromuscular mechanisms thus promoting locomotor activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
124
0
5

Year Published

1992
1992
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 249 publications
(131 citation statements)
references
References 6 publications
2
124
0
5
Order By: Relevance
“…Avermectins are compounds produced by a novel species S. avermitilis isolated from soil. They were found to be an effective antihelminthic compound earlier (Burg et al, 1979), but later it was also found to be a potent insecticide, acaricide and nematicide (Putter et al, 1981).…”
Section: Actinomycetes and Its Metabolitesmentioning
confidence: 99%
“…Avermectins are compounds produced by a novel species S. avermitilis isolated from soil. They were found to be an effective antihelminthic compound earlier (Burg et al, 1979), but later it was also found to be a potent insecticide, acaricide and nematicide (Putter et al, 1981).…”
Section: Actinomycetes and Its Metabolitesmentioning
confidence: 99%
“…Os produtos mais utilizados são aqueles à base de avermectinas (abamectina), produzidas por Streptomyces avermictilus (Putter et al, 1981), registrados para a cultura do algodão em 2006. Outro produto registrado, em 2007, nos EUA, para tratamento de sementes em algodão é thiodicarb .…”
Section: O Nematoide Reniforme (Rotylenchulus Reniformisunclassified
“…Yamazaki et al (1989) found that ivermectin is an agonist for the GABA concentration. Abamectin acts on gamma amino butyric acid (GABA) and glutamate-gated chloride channels, leading to activation of the chloride ion channel at higher concentrations and paralysis of pests (Putter, 1981, Bloomquist, (2001. CONCLUSION The present results showed that earthworm is quite sensitive to the toxicity and, could be used as biomarkers for the different groups of insecticides which are introduced into the soil system.…”
Section: L-glutamic Acid and Gaba Concentrationsmentioning
confidence: 99%